Preventive Effect of Central Administration of Venlafaxine on Morphine Physical Dependence, Nociception, and Blood Cortisol Level in Rat - Motaghinejad, Majid (Int J Prev Med, 2014)
BACKGROUND: Chronic abuse of opiates induces dependency, but the neurobiological mechanisms of this event remain unclear. The aim of this study was to evaluate the effects of intracerebroventricular of venlafaxine on the morphine dependence and pain perception. METHODS: A total of 80 adult male rats were divided into two major groups: (1) 40 of them was divided into groups of positive control (morphine dependent) negative control (received saline) and morphine dependent groups under treatment by central administration of venlafaxine at various dosages (25, 50, or 100 μg), after drug treatment total withdrawal index (TWI), latency time of withdrawal syndrome expression and blood cortisol as marker of anxiety were measured and compared with positive control and negative control. (2) Forty rats were grouped in control; indometacin treated (5 mg/kg) and grouped which received central administration of venlafaxine at three doses (25, 50, or 100 μg) and then pain perception and expression was assessed in the writhing test (acetic acid induced abdominal constriction), tail flick, and hot plate test. RESULTS: Central administration of three doses (25, 50, or 100 μg,) of venlafaxine attenuates TWI to 47 ± 1.2, 38 ± 1.5, and 23 ± 1.1 and decrease blood cortisol level to 14 ± 1, 13.75 ± 0.5, and 12.5 ± 0.8, this decreases was significant in comparison with the positive control group (P < 0.05). Central administration of venlafaxine at mentioned doses significantly attenuates pain response with 37%, 24%, and 20% inhibition in writhing test, 69%, 34%, and 23% inhibition in hot plate test, and 29%, 23%, and 15% inhibition in tail flick test in comparison with control group (P < 0.05). CONCLUSIONS: This study suggested that central administration of venlafaxine attenuated morphine withdrawal index and can be effective in modulation of pain that was induced by morphine dependency.